A cross-sectional survey of the pharmacy workforce in general practice in Scotland. (19th September 2019) - Stewart, Derek; Maclure, Katie; Newham, Rosemary; Gibson-Smith, Kathrine; Bruce, Rachel; Cunningham, Scott; Maclure, Andrew; Fry, Sarah; Mackerrow, James; Bennie, Marion
Abstract: Background: In Scotland, there has been significant investment in pharmacy teams in general medical practices over recent years, aligned to current government policy. Objectives: To characterize the national pharmacy workforce including activities undertaken, perceived competence and confidence, as well as perception of integration of the intervention. Methods: A cross-sectional survey of all pharmacists and pharmacy technicians in general practices. Survey items were demographics, activities undertaken and experiences. The NoMAD tool (Improving the Normalization of Complex Interventions) was included as a measure of perspectives of implementation. Post-piloting, a questionnaire link was sent to all pharmacists ( n = 471) and pharmacy technicians ( n = 112). A total NoMAD score was obtained by assigning 1 (strongly disagree) to 5 (strongly agree) to each item. Results: Responses were received from 393 (83.4%) pharmacists and 101 (91.8%) pharmacy technicians. Three quarters of pharmacists (74.6%) and pharmacy technicians (73.3%) had been qualified for over 10 years. Two-thirds of pharmacists (68.4%) were independent prescribers, with three quarters (72.3%) currently prescribing. Respondents worked in a median of two practices and were providing a range of activities including medication/polypharmacy reviews, medicines reconciliation, prescribing efficiencies and training. Respondents reported high levels of competence and confidence (median 8, scale 0–10 highest). Median NoMAD total score (scale 20–100 highest, Cronbach's alpha 0.89) was 80 for pharmacists and 75 for pharmacy technicians, P ≤ 0.001. Conclusions: The general practice pharmacy workforce in Scotland is experienced, well-qualified and integrated within general practices, delivering a range of activities. These findings have implications for workforce planning and future education and training.